2005
DOI: 10.1093/jac/dki232
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Streptococcus mutans biofilms to photodynamic therapy: an in vitro study

Abstract: Photodynamic therapy may be a useful approach in the treatment of dental plaque-related diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
197
7
42

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 266 publications
(256 citation statements)
references
References 28 publications
10
197
7
42
Order By: Relevance
“…Recently, alternative light sources, such as LED, have been successfully used in PDT. 25,26,44 In the present investigation, LED was used as a light source because of its ability to irradiate larger areas than is possible with collimated laser light. Moreover, LED technology is simpler and has a lower cost than laser.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, alternative light sources, such as LED, have been successfully used in PDT. 25,26,44 In the present investigation, LED was used as a light source because of its ability to irradiate larger areas than is possible with collimated laser light. Moreover, LED technology is simpler and has a lower cost than laser.…”
Section: Discussionmentioning
confidence: 99%
“…However, light sources with simpler technology and lower cost than lasers, such as light-emitting diodes (LED), have been successfully applied in PDT. 25,26 In addition, there are different colors of LED light, with radiations covering almost the entire visible electromagnetic spectrum. Investigations with the aim of confirming the effectiveness of antimicrobial PDT in animal models are scarce.…”
mentioning
confidence: 99%
“…The efficacy of PDT with erythrosine in S. mutans has been previously studied 16,17) . Wood et al 16) compared the use of three different photosensitizing agents: erythrosine, Photofrin, and methylene blue at 22 μ M for each dye concentration to photosensitize the S. mutans biofilm, using 400 W tungsten lamp.…”
Section: ⅳ Discussionmentioning
confidence: 99%
“…Previous studies have shown that PDT using erythrosine is capable of killing oral bacteria [15][16][17][18] . Recently, Park et al 15) proved that PDT effect of erythrosine as a photosensitizer and dental halogen curing unit as a light source to the planktonic condition of S. mutans.…”
Section: ⅰ Introductionmentioning
confidence: 99%
“…Previous studies have examined the effects of PDT on single-species biofilms using streptococci to model supragingival plaque in conditions associated with onset of dental caries (Zanin et al, 2005(Zanin et al, , 2006 and Streptococcus pyogenes to model a skin biofilm . However, PDT also offers a promising, non-invasive treatment for periodontal disease.…”
Section: Introductionmentioning
confidence: 99%